2020
DOI: 10.1021/acssuschemeng.0c03950
|View full text |Cite
|
Sign up to set email alerts
|

Direct Quantification of Lignin in Liquors by High Performance Thin Layer Chromatography-Densitometry and Multivariate Calibration

Abstract: A method for lignin quantification is presented that is based on densitometry and multivariate calibration by partial least squares (PLS). Densitometry removes interferences otherwise caused by undissolved liquor components and solvents, while multivariate calibration accounts for interferences by other sample components, such as extractives or chromophoric compounds. Method validation predicted a bias very close to 0% and an uncertainty of 10% (kraft) to 20% and less (lignosulfonate). In trials with three ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Switching to higher detection wavelengths (410 and 475 nm) resulted in linear, more robust calibrations, while good signal intensities were still maintained (Figures 1 and S1). Khaliliyan et al 14 reported a similar improvement in lignin quantification in BLs when opting for higher detection wavelengths. Detailed information about the calibration fitting functions can be found in Table S1.…”
Section: Effect Of Detection Wavelength and Concentrationmentioning
confidence: 99%
See 4 more Smart Citations
“…Switching to higher detection wavelengths (410 and 475 nm) resulted in linear, more robust calibrations, while good signal intensities were still maintained (Figures 1 and S1). Khaliliyan et al 14 reported a similar improvement in lignin quantification in BLs when opting for higher detection wavelengths. Detailed information about the calibration fitting functions can be found in Table S1.…”
Section: Effect Of Detection Wavelength and Concentrationmentioning
confidence: 99%
“…Fast and robust quantification of the lignin contents in pulping liquors is needed for optimized process control of the evaporation plant, lignin extraction, recovery boiler, or other subsequent biorefinery operations. 13,14 A major bottleneck for the required high analytical throughput is the tedious and timeconsuming isolation and separation of lignin from the pulping liquor prior to analysis. Industrially, lignin isolation is done by acidic precipitation (e.g., Lignoboost, Lignoforce) to separate lignin from the other BL constituents, 15−17 which allows recovery of reasonably pure technical lignin�as the basis of the many future applications.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations